2009
DOI: 10.14254/2071-789x.2009/2-2/2
|View full text |Cite
|
Sign up to set email alerts
|

Allies or Rivals? Shaping Images of Co-Host Countries via Common Mega Event. The Case of Poland and Ukraine and Euro 2012

Abstract: ABSTRACT. This paper discusses the determinants of shaping images of host countries through one, shared mega event. In particularly, it presents possible relationships between the overlapping sets of images of event organizer, host countries, host cities and other country's destinations and consequently, between their communication strategies. Identification of the these interdependencies, areas of competition and possible synergies is vital for destinations in order to capitalize on the common mega event -tog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Additionally, it is widely recognized that destination image plays a substantial influence on tourists' decision-making process (Luvsandavaajav et al, 2022), including the destination selection, the length of stay, the type of activities, and the overall satisfaction with the experience ( Souiden et al, 2017). The destination image can be shaped via actual experiences like real visits or indirect experiences like exposure to marketing activities (Florek, 2009). Zhang et al (2014), SaatÇİ (2020), Ragab et al (2020), and Vera and Chang (2022) believe that the destination image formed after visiting the destination is more actual, intricate, and diverse from the image that was formed before visiting.…”
Section: Events As a Destination-based Marketing Strategy And Destina...mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, it is widely recognized that destination image plays a substantial influence on tourists' decision-making process (Luvsandavaajav et al, 2022), including the destination selection, the length of stay, the type of activities, and the overall satisfaction with the experience ( Souiden et al, 2017). The destination image can be shaped via actual experiences like real visits or indirect experiences like exposure to marketing activities (Florek, 2009). Zhang et al (2014), SaatÇİ (2020), Ragab et al (2020), and Vera and Chang (2022) believe that the destination image formed after visiting the destination is more actual, intricate, and diverse from the image that was formed before visiting.…”
Section: Events As a Destination-based Marketing Strategy And Destina...mentioning
confidence: 99%
“…Previous research indicates that tourists' affective responses to a destination are influenced by their perceptions of its natural beauty, climate, people, and culture Extant research showed that consumer decision behaviour and repeat traveller behaviour are both influenced by the experiential aspects of consumption (Kaplanidou, 2009). Furthermore, destination image can also impact the loyalty of tourists and their retention (Florek, 2009;Hossain et al, 2022). A positive image can lead to repeat visits, recommendations of destinations to others, and positive reviews, which can all contribute to the growth of the tourism industry in a destination 2022) pointed out that a tourist who constructs a positive image of an event makes an affirmative assessment of the host destination image and is more likely to have upcoming visit intentions.…”
Section: Destination Image and Behavioural Intentionmentioning
confidence: 99%
See 1 more Smart Citation